2019
DOI: 10.1073/pnas.1903870116
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the material properties and rRNA processing function of the nucleolus using light

Abstract: The nucleolus is a prominent nuclear condensate that plays a central role in ribosome biogenesis by facilitating the transcription and processing of nascent ribosomal RNA (rRNA). A number of studies have highlighted the active viscoelastic nature of the nucleolus, whose material properties and phase behavior are a consequence of underlying molecular interactions. However, the ways in which the material properties of the nucleolus impact its function in rRNA biogenesis are not understood. Here we utilize the Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 55 publications
1
62
0
Order By: Relevance
“…In addition, it appears that molecular dynamics of NCL is regulated by HDACs upon acetyl-CoA depletion (S7D and S7E Fig). As the molecular dynamics in a condensate can be seen as an indicator for its material property, these observations imply alterations in the phase material property of the nucleolus, which is reported to be tightly linked to the nucleolar function [86]. It would be worth noting that the clustered lysine residues that we found as TMP195-sensitive acetylation sites were located in the N-terminal intrinsically disordered region (IDR) of NCL ( S7C Fig) [87].…”
Section: Discussionmentioning
confidence: 54%
“…In addition, it appears that molecular dynamics of NCL is regulated by HDACs upon acetyl-CoA depletion (S7D and S7E Fig). As the molecular dynamics in a condensate can be seen as an indicator for its material property, these observations imply alterations in the phase material property of the nucleolus, which is reported to be tightly linked to the nucleolar function [86]. It would be worth noting that the clustered lysine residues that we found as TMP195-sensitive acetylation sites were located in the N-terminal intrinsically disordered region (IDR) of NCL ( S7C Fig) [87].…”
Section: Discussionmentioning
confidence: 54%
“…In the absence of bound NPM1-C, the ferritin core is strongly excluded from nucleoli, with a ΔG tr of approximately +1.4 kcal/mol ( Fig. S7), consistent with large noninteracting assemblies being excluded from the nucleolus and other condensates [22][23][24] . However, upon increasing the valence of the core with light activation, its partitioning into the nucleolus increases, implying a more negative transfer free energy.…”
mentioning
confidence: 68%
“…Hence, the result may suggest that the redistribution of mass inside the nucleus is caused by the formation of nucleoli, thus reducing the mass density of nucleoplasm. This could be further investigated by measuring the mass density of nucleoplasm and nucleoli whose material properties can be modulated by an optogenetic gelation strategy (62). Recent studies have shown that the cell growth rate is sizedependent and exhibits exponential growth (63)(64)(65), and the size of nucleoli scales with that of cells while nuclei grow slower in the development of C. elegans embryo (66).…”
Section: Discussionmentioning
confidence: 99%